On Heyting Algebra - Chakrabarti, Swapan Kumar; Yadav, R. N.; Pathak, S. R. (International Journal For Research In Mathematics And Statistics, 2020)
In mathematics Heyting algebras are special partially ordered sets that constitute a generalisation of Boolean algebra. It is named after Arend Heyting. Heyting algebra arises as models of intuitionistic logic, a logic in which the law of excluded middle does not in general hold. Thus complete Heyting algebra is a central object of study in pointless topology.